Safety and Tolerability of Difelikefalin for the Treatment of Moderate to Severe Pruritus in Hemodialysis Patients: Pooled Analysis From the Phase 3 Clinical Trial ProgramPlain-Language Summary - Steven Fishbane; Warren Wen; Catherine Munera; Rong Lin; Sukirti Bagal; Kieran McCafferty; Frédérique Menzaghi; Joana Goncalves (Kidney Medicine, 2022)
Rationale & Objective: We report a pooled safety analysis of intravenous difelikefalin in participants with moderate to severe chronic kidney disease–associated pruritus (CKD-aP) treated by hemodialysis in 4 phase 3 clinical studies. Study Design: KALM-1 and KALM-2 were randomized, double-blind, placebo-controlled, pivotal phase 3 studies; CLIN3101 (52 weeks) and CLIN3105 (12 weeks) were open-label studies. Setting & Participants: Adults with moderate to severe CKD-aP treated by hemodialysis in North America, Europe, and the Asia-Pacific region. Intervention: At least 1 intravenous placebo or difelikefalin dose of 0.5 mcg/kg for up to 64 weeks. Outcomes: Safety. Results: Safety analyses were conducted with 848 participants in the placebo-controlled cohort (424 participants each in the difelikefalin and placebo groups) and in 1,306 participants in the all-difelikefalin-exposure cohort. In the placebo-controlled cohort, the most commonly reported treatment-emergent adverse events (TEAEs), occurring in ≥2% of participants receiving difelikefalin and with a ≥1% higher incidence than placebo, were diarrhea (9.0% and 5.7%, respectively); dizziness (6.8% and 3.8%, respectively); nausea (6.6% and 4.5%, respectively); gait disturbances, including falls (6.6% and 5.4%, respectively), hyperkalemia (4.7% and 3.5%, respectively); headache (4.5% and 2.6%, respectively); somnolence (4.2% and 2.4%, respectively); and mental status changes (3.3% and 1.4%, respectively). These were mostly mild or moderate, with few leading to discontinuation. Incidence rates of TEAEs, serious TEAEs, and discontinuations because of TEAEs did not increase with long-term exposure. Three participants (0.7%) in the difelikefalin group and 5 participants (1.2%) in the placebo group died during the study. Limitations: Pooled data from studies with different designs. Conclusions: Intravenous difelikefalin demonstrated an acceptable safety profile, was generally well tolerated with long-term use, and may address the unmet treatment need for patients with CKD-aP treated by hemodialysis. Funding: Cara Therapeutics, Inc. Trial Registration: KALM-1 is registered as NCT03422653, KALM-2 as NCT03636269, CLIN3101 as NCT03281538, and CLIN3105 as NCT03998163.